SINTESIS ANTIOKSIDAN 4,6-DIALIL-2-METOKSIFENOL DARI ALIL EUGENOL MELALUI PENATAAN ULANG CLAISEN - Suryanto, Edi; Anwar, Chairil (Sam Ratulangi University, 2008)
The objectives of this study was to synthesized 4,6-diallyl-2-methoxyphenol (DMP) from allyl eugenol by Claisen rearrangement. The reaction was carried out at temperature 170-200oC and the reaction time was 30 minutes. The synthesis of DMP by heating at 170-200oC for a certain period of time appears to be a fairly good and simple method. The synthesis compounds were elucidated by infrared (IR), nuclear magnetic resonance (1H-NMR), and mass spectrometry (MS) techniques. Antioxidant activity evaluated the based on the heating of coconut oil. At higher temperatures of reaction the yield will be higher and at the reaction time 30 minutes will produce will produce higher yield which was 59,19%. The gas chromatographic analysis showed that the purity of DMP was 96,45% The structure of 4,6-diallyl-2-methoxyphenol was identified by IR spectrometry which shows strong absorption at 3527 cm-1 indicating hydroxyl group from the phenolic compound and 1H NMR spectra showed that the number of protons of aromatic ring was two hydrogen while the mass spectrometry showed the molecular ion peak at m/z 204 as base peak and absence of peak at (M-41)+ as the indicator of ally eugenol. The addition of DMP at concentration 200 ppm in coconut oil exhibited excellent inhibition of oxidation reaction more than BHT as control positive. The result concluded that 4,6-diallyl-2-methoxyphenol had antioxidant activity on heating of coconut oil at 80oC for 30 day.